Transformational Leadership in Pesantren on as Sa'idah, Al Matuq, and Sunanul Huda Boarding School - Supendi, Pepen; Hasanah, Aan; Mahmud, Mahmud (Jurnal Pendidikan Islam, 2018)
The leadership of Kiai plays an essential act in the Institution structure of Pesantren. The important enrolled of Kiai is a good man on life purpose, a change agent, a negotiator with advice, and a coach calm. The reformer Kiai does on leadership with transformation ideas on based charisma attitude and intellectual ideology. The research method is qualitative research with a phenomenology approach. The research subjects consist of Kiai, boarding school administrators, students, people residents around pesantren. The respondents are as many as 60 people. The Research locations are at as sa'idah, Al Matuq, and Sunanul Huda Pesantren. With this point, the paper will need to explain the leadership of Kiai Pesantren especially in order to support the quality management of Pesantren on educational proses.